Theoretical study on low-lying electronic states of CP radical: Energy levels, Einstein coefficients, Franck-Condon factors and radiative lifetimes. (June 2019) - Qin, Zhi; Zhao, Junming; Liu, Linhua
Highlights: Transition dipole moments between different Λ-S states for CP are calculated. Radiative transition probabilities for nineteen dipole-allowed transitions are discussed. The spectral range for each band system is determined. Rotationless radiative lifetimes of vibrational levels for some states are evaluated. Abstract: The state-of-the-art ab initio -based valence internally contracted multireference configuration-interaction (icMRCI) method, including the Davidson correction, core-valence correction and scalar relativistic correction and the basis-set extrapolation, is used to calculate the potential energy curves (PECs) of the X 2 Σ +, B 2 Σ +, A 2 Π, 1 2 Σ −, 1 2 Δ, 2 2 Δ, 2 2 Σ −, 1 4 Σ +, 2 4 Σ +, 1 4 Π, 1 4 Δ, 1 4 Σ −, 2 4 Δ, 2 4 Σ − 1 6 Σ + and 2 6 Σ + electronic states for CP radical. We also calculate the transition dipole moments (TDMs), Einstein coefficients and Franck-Condon factors for nineteen dipole allowed transitions between these sixteen states. The PECs are used to fit spectroscopic parameters, which are in excellent agreement with previous experimental and theoretical ones. The computed Franck-Condon factors also agree quite well with accurate semi-empirical results for the A 2 Π-X 2 Σ + and B 2 Σ + -X 2 Σ + systems. Such good agreement implies that the results are accurate enough to assist identification of the spectra from astrophysical sources. Large amounts of energy levels and transition data of high accuracy are provided in this work for CP radical of astrophysical interest, where experimental data are still scarce.